Verification of Economic and Agricultural Indicators With the Use of Statistical Methods on the Example of Individual Farms (Agricultural Engineering, 2016)
The paper describes basic methodology assumptions related to construction of Bayesian networks. The paper aims at preparation of data for modeling to obtain fresh knowledge on economic and agricultural database and will constitute the first stage of research. Variables (economic and agricultural indicators) with discreet values were used for analysis with the use of two step grouping technique and previous non-typical data were explored. The research was carried out on the group of three hundred individual fanns from Malopolskie and Swiçtokrzyskie Voiovedship. The knowledge obtained from analyses will be used in practice in agricultural engineering in order to support agricultural activity.